Clinical Impact of Stump Closure Reinforced With Hemopatch on the Prevention of Clinically Relevant Pancreatic Fistula After Distal Pancreatectomy: A Multicenter Randomized Trial. Issue 1 (10th March 2021) - Uranues, Selman; Fingerhut, Abraham; Belyaev, Orlin; Zerbi, Alessandro; Boggi, Ugo; Hoffmann, Matthias W.; Reim, Daniel; Esposito, Alessandro; Primavesi, Florian; Kornprat, Peter; Coppola, Roberto; Fragulidis, Georgio P.; et al.
Abstract : Introduction: Postoperative pancreatic fistula (POPF) is the most dreaded complication after distal pancreatectomy (DP). This multicenter randomized trial evaluated the efficacy, safety, and tolerance of Hemopatch in preventing clinically relevant (grades B/C according to the ISGPS classification) POPF after DP. Material and methods: After stump closure, patients were randomized to affix Hemopatch to the stump or not. Statistical significance was set at 0.025. Clinical significance was defined as the number of patients needed to treat (NNT) to avoid 1 B/C POPF. Results: Of 631 eligible patients, 360 were randomized and 315 analyzed per protocol (155 in the standard closure group; 160 in the Hemopatch group). The rates of B/C POPF (the primary endpoint) were 23.2% and 16.3% ( P = 0.120), while the number of patients with 1 or more complications (including patients with B/C POPF) was 34.8% and 24.4% ( P = 0.049) in the standard and Hemopatch groups, respectively. In patients with hand-sewn stump and main duct closure, the rates were 26.2% versus 10.0% ( P = 0.014) and 23.3% versus 7.7% ( P = 0.015) in the standard and Hemopatch groups, respectively. The NNT in these 2 subgroups was 6 and 6.4, respectively. Conclusion: The results of the first randomized trial evaluating Hemopatch-reinforced pancreatic stump after DP to prevent type B/C POPF do not allow us to conclude that the risk of B/C POPF was lower. Based on the NNT, however, routine use of Hemopatch after DP may result in fewer complications (including POPF) overall, especially in cases with hand-sewn closure of the pancreatic stump or main pancreatic duct. Abstract : Mini-abstract: This multicenter randomized study evaluated the efficacy, safety, and tolerance of Hemopatch in preventing clinically relevant (types B and C) postoperative pancreatic fistula (B/C POPF) after distal pancreatectomy (DP). Clinical significance was defined as the number of patients needed to treat to avoid 1 POPF. Hemopatch reduced the rate of POPF after DP. Although the difference was statistically significant only in patients with hand-sewn stumps and when the main pancreatic duct was closed, the clinical signification was that routine use after DP would result in fewer complications and less associated costs in these 2 settings.